National Defense Education and Training Strategies in Utilizing Demographic Bonuses to Strengthen National Defense - Fatwa Budiyanti; Afrizal Hendra; Almuchalif Suryo; Muhammad Noor Gibran (International Journal of Technology and Education Research, 2026)
Defending the country, supported by love for the homeland, is increasingly important in the face of global threats such as terrorism, cyber conflicts, and natural disasters. The demographic bonus provides great potential for the younger generation, especially generations Y and Z, to strengthen defense through national defense education that integrates technology, digital literacy, and adaptation to modern challenges. The purpose of this study is to analyze the Optimization of Strengthening the Competitiveness of National Films to Maintain Cultural Resilience of National Defense Education and Training Strategies in Utilizing Demographic Bonuses to Strengthen National Defense. The method used in this study is qualitative with SWOT analysis. The results of the research show that first, integrating national defense education in formal and digital curricula, utilizing educational infrastructure and technology to reach the young generation throughout Indonesia, including remote areas. Second, increasing private sector participation through cooperation that supports training and facilities, expanding opportunities for communities to contribute to the country's defense. Third, strengthening international collaboration in defense education, utilizing cooperation with developed countries for knowledge and technology transfer, improving the quality of Indonesia's national defense program through student exchanges and international training.